Remote sensing with polarimetric radar - Mott, Harold (IEEE Press Wiley-Interscience, 2007)
This book presents the principles central to understanding polarized wave transmission, scattering, and reception in communication systems and polarimetric and non-polarimetric radar. Readers gain new insight into the methods for remotely gathering data about the earth's surface and atmosphere with polarimetric synthetic-aperture radar and polarimetric interferometry, including the changes that take place with seasons, floods, earthquakes, and other natural phenomena.